2019
DOI: 10.3390/polym11111809
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based Coating Materials Derived from Acetoacetylated Soybean Oil and Aromatic Dicarboxaldehydes

Abstract: Bio-based coating materials were prepared from epoxidized soybean oil as a renewable source. Acetoacetylated soybean oil was synthesized by the ring-opened and transesterification reaction of epoxidized soybean oil, and its chemical structure was characterized by nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FTIR), gel permeation chromatography (GPC), and rheometric viscosity analyses. On the basis of acetoacetylated soybean oil, several bio-based coating materials were prepared us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…[1][2][3][4] Vegetable oils, as renewable resources, have unique chemical structures containing hydroxyls, esters, unsaturated sites, and other functional groups, and these can be modied to make low molecular weight polymeric materials for a range of versatile applications. [5][6][7][8][9] Acetoacetyl chemistry is interesting to use to prepare thermoset resins because acetoacetate functional groups can react with various groups, [10][11][12][13] including aldehydes, 14 isocyanates, 15 acrylates, 16 and amines. 17 Although many thermoset resins have been prepared using acetoacetate chemistry and amines, only a few studies have been reported on the synthesis of biobased coating materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Vegetable oils, as renewable resources, have unique chemical structures containing hydroxyls, esters, unsaturated sites, and other functional groups, and these can be modied to make low molecular weight polymeric materials for a range of versatile applications. [5][6][7][8][9] Acetoacetyl chemistry is interesting to use to prepare thermoset resins because acetoacetate functional groups can react with various groups, [10][11][12][13] including aldehydes, 14 isocyanates, 15 acrylates, 16 and amines. 17 Although many thermoset resins have been prepared using acetoacetate chemistry and amines, only a few studies have been reported on the synthesis of biobased coating materials.…”
Section: Introductionmentioning
confidence: 99%
“…There are many publications on the double bond epoxidation of fatty acids by different methods for further synthesizing polyols by ring-opening reactions with alcohols [ 8 , 9 , 10 , 11 ]. In a couple of studies, these polyols are used as a part of component A to produce polyurethanes [ 3 , 7 , 12 , 13 , 14 , 15 ]. Isocyanates are used as component B in conventional polyurethane production.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyl groups of polyols can be converted to β-ketoesters to obtain polymers with acrylates by the Michael reaction. Although the method is known, the research has mainly been conducted for coating materials [ 12 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations